2013
DOI: 10.1542/peds.2013-0978
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation of Preterm Neonates With Limited Versus High Oxygen Strategy

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Preterm infants can be successfully resuscitated with ,100% oxygen (O 2 ); however, initiation with room air remains controversial. Current Neonatal Resuscitation Program (NRP) guidelines suggest using air or blended O 2 to titrate O 2 to meet target preductal saturation goals. WHAT THIS STUDY ADDS:This is the first trial to compare a limited O 2 strategy to target NRP-recommended transitional goal saturations versus a high O 2 strategy in preterm infants. The limited O 2 strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
128
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(139 citation statements)
references
References 44 publications
2
128
0
4
Order By: Relevance
“…The quality of evidence was downgraded for imprecision. 175,[177][178][179][180] We found very-low-quality evidence from 1 cohort study including 125 subjects showing no benefit to beginning resuscitation with high-oxygen as compared with low-oxygen concentration (RR, 1.31; 95% CI, 0.41-4.24). The quality of evidence was downgraded for serious imprecision.…”
Section: Consensus On Sciencementioning
confidence: 88%
See 1 more Smart Citation
“…The quality of evidence was downgraded for imprecision. 175,[177][178][179][180] We found very-low-quality evidence from 1 cohort study including 125 subjects showing no benefit to beginning resuscitation with high-oxygen as compared with low-oxygen concentration (RR, 1.31; 95% CI, 0.41-4.24). The quality of evidence was downgraded for serious imprecision.…”
Section: Consensus On Sciencementioning
confidence: 88%
“…The quality of evidence was downgraded for imprecision. [174][175][176][177][178][179][180] When limited to randomized clinical trials with concealed allocation and oxygen targeting as a cointervention, we found moderate-quality evidence from 5 trials enrolling 468 subjects showing no benefit to beginning resuscitation with a high-oxygen concentration as compared with lowoxygen concentration (RR, 1.33; 95% CI, 0.68-2.62). The quality of evidence was downgraded for imprecision.…”
Section: Consensus On Sciencementioning
confidence: 91%
“…125,128,129 When oxygen targeting was used as a cointervention, the oxygen concentration of resuscitation gas and the preductal oxygen saturation were similar between the high-oxygen and lowoxygen groups within the first 10 minutes of life. 125,[128][129][130] In all studies, irrespective of whether air or high oxygen (including 100%) was used to initiate resuscitation, most infants were in approximately 30% oxygen by the time of stabilization. Resuscitation of preterm newborns of less than 35 weeks of gestation should be initiated with low oxygen (21% to 30%), and the oxygen concentration should be titrated to achieve preductal oxygen saturation approximating the interquartile range measured in healthy term infants after vaginal birth at sea level 123 (Class I, LOE B-R).…”
Section: Preterm Nrp 864mentioning
confidence: 96%
“…[124][125][126][127][128][129][130] Similarly, in the subset of studies that evaluated these outcomes, no benefit was seen for the prevention of bronchopulmonary dysplasia, 125,[127][128][129][130] IVH, 125,[128][129][130] or retinopathy of prematurity. 125,128,129 When oxygen targeting was used as a cointervention, the oxygen concentration of resuscitation gas and the preductal oxygen saturation were similar between the high-oxygen and lowoxygen groups within the first 10 minutes of life. 125,[128][129][130] In all studies, irrespective of whether air or high oxygen (including 100%) was used to initiate resuscitation, most infants were in approximately 30% oxygen by the time of stabilization.…”
Section: Preterm Nrp 864mentioning
confidence: 99%
“…[124][125][126][127][128][129][130] Similarly, in the subset of studies that evaluated these outcomes, no benefit was seen for the prevention of bronchopulmonary dysplasia, 125,[127][128][129][130] IVH, 125,[128][129][130] or retinopathy of prematurity. 125,128,129 When oxygen targeting was used as a cointervention, the oxygen concentration of resuscitation gas and the preductal oxygen saturation were similar between the high-oxygen and low-oxygen groups within the first 10 minutes of life. 125,[128][129][130] In all studies, irrespective of whether air or high oxygen (including 100%) was used to initiate resuscitation, most infants were in approximately 30% oxygen by the time of stabilization.…”
Section: Preterm Nrp 864mentioning
confidence: 99%